2020
DOI: 10.1088/1755-1315/548/3/032034
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of data on air temperature based on current weather data sets for 2007-2019

Abstract: Modern tasks in the field of agriculture require meteorological information of high spatial and temporal resolution. In this study, air temperature was compared using the CRU_TS, ERA5-Land, and GFS datasets in the study area for the period from 2007 to 2019. The information obtained showed a high level of correlation (0.9) of the considered data sets for the study period. However, a more detailed analysis revealed that there may be months when the air temperature values of different data sets can vary signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The CRU-TS dataset (upon which the CCKP estimates are based) is observational, whereas the ERA-5 data (upon which AREAdata is based) is a reanalysis combining forecasting model estimates with observations to provide spatially and temporally finer-grained climate estimates. Previous work has found similar overall correlations between the CRU-TS and ERA-5 data (approx 0.9) 22 , however these datasets can vary significantly at particular times and in particular places 22,23 . In particular, there is likely a warm bias in the ERA-5 reanalysis in recent years due to lesser representation of snow on top of sea ice 24 , which may explain the deviations we observe here.…”
Section: Technical Validationmentioning
confidence: 63%
“…The CRU-TS dataset (upon which the CCKP estimates are based) is observational, whereas the ERA-5 data (upon which AREAdata is based) is a reanalysis combining forecasting model estimates with observations to provide spatially and temporally finer-grained climate estimates. Previous work has found similar overall correlations between the CRU-TS and ERA-5 data (approx 0.9) 22 , however these datasets can vary significantly at particular times and in particular places 22,23 . In particular, there is likely a warm bias in the ERA-5 reanalysis in recent years due to lesser representation of snow on top of sea ice 24 , which may explain the deviations we observe here.…”
Section: Technical Validationmentioning
confidence: 63%
“…However, ERA5-Land offers a higher spatiotemporal resolution and better hydrological representation compared with other remote sensing and reanalysis datasets, making it widely applied in global and regional drought research [89][90][91][92]. For instance, Dergunov et al [93] compared the temperature data of ERA5-Land, Climate Research Unit gridded time series (CRU TS), and the Global Forecast System (GFS) and found that although the three products had a high correlation with temperature, the ERA5-Land dataset was more suitable for capturing small changes due to its higher spatiotemporal resolution. The evaluation of soil moisture and surface runoff data by previous studies indicated the outperformance of the ERA5 product [94].…”
Section: Uncertainties Limitations and Future Directionmentioning
confidence: 99%
“…ERA5_Land data are updated and easily accessible with high spatial and temporal resolution and are now widely used for flood and drought prediction (Dergunov & Yakubailik, 2020;Huang et al, 2021).…”
Section: Spatial Pattern Prediction Of Sm and Drought Grade In The Ssnpmentioning
confidence: 99%